2011
DOI: 10.1007/s10646-011-0756-4
|View full text |Cite
|
Sign up to set email alerts
|

MercNet: a national monitoring network to assess responses to changing mercury emissions in the United States

Abstract: A partnership of federal and state agencies, tribes, industry, and scientists from academic research and environmental organizations is establishing a national, policy-relevant mercury monitoring network, called MercNet, to address key questions concerning changes in anthropogenic mercury emissions and deposition, associated linkages to ecosystem effects, and recovery from mercury contamination. This network would quantify mercury in the atmosphere, land, water, and biota in terrestrial, freshwater, and coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…Higher atmospheric Hg deposition and soil Hg concentrations and pools were found in the ADR and the CATPOC regions. These two subregions likely receive higher atmospheric Hg deposition due to their closer proximity to elevated Hg emission sources in the Midwest and urban centers of the Northeast (Choi et al 2008, Schmeltz et al 2011 and their relatively higher elevations (Yu et al 2011). The lack of significant correlations between current atmospheric Hg deposition and soil Hg concentrations and pools has been reported in previous investigations (Obrist et al 2011).…”
Section: Factors Influencing Spatial Patterns Of Hgmentioning
confidence: 66%
See 1 more Smart Citation
“…Higher atmospheric Hg deposition and soil Hg concentrations and pools were found in the ADR and the CATPOC regions. These two subregions likely receive higher atmospheric Hg deposition due to their closer proximity to elevated Hg emission sources in the Midwest and urban centers of the Northeast (Choi et al 2008, Schmeltz et al 2011 and their relatively higher elevations (Yu et al 2011). The lack of significant correlations between current atmospheric Hg deposition and soil Hg concentrations and pools has been reported in previous investigations (Obrist et al 2011).…”
Section: Factors Influencing Spatial Patterns Of Hgmentioning
confidence: 66%
“…The historical record obtained from paleolimnological studies suggests that atmospheric Hg deposition has increased steadily (two-to three-fold) since the onset of industrialization until the late 1900s (Swain et al 1992, Fitzgerald et al 1998, Lorey and Driscoll 1999, Schuster et al 2002, Biester et al 2007). Studies have also indicated that regional Hg deposition has decreased in recent decades, which is coincident with efforts to control Hg emissions in North America (Engstrom and Swain 1997, Drevnick et al 2011, Schmeltz et al 2011. Studies suggest that Hg deposition Notes: The deposition before industrialization (,1850) was considered to be steadfast at each of the subregions.…”
Section: Reconstruction Of Historical Hg Depositionmentioning
confidence: 99%
“…Widespread, and often elevated, biological Hg exposure implies the need for Hg monitoring at a regional and national scale that can track changes in Hg emissions and effluents. Long-term Hg monitoring across the Great Lakes region by the Mercury Deposition Network needs to be supplemented with components as described in the proposed National Mercury Monitoring Program or MercNet (Mason et al 2005;Harris et al 2007;USEPA 2008;Schmeltz et al 2011). Such a standardized network is necessary to inform federal and state Hg-related policies, provide data for predictive models, and characterize the biological effects in the United States from the redistribution of anthropogenic Hg on the landscape.…”
Section: Policy and Management Implicationsmentioning
confidence: 99%
“…Mercury (Hg) is a highly toxic pollutant released from anthropogenic sources such as waste from chemical plants and emissions from coal burning power plants (Scheuhammer et al, 2007;Schmeltz et al, 2011;Walker, 2014). In aquatic habitats mercury is methylated into methylmercury (MeHg), which increases its toxicity (Lindqvist et al, 1991;Bloom, 1992).…”
Section: Introductionmentioning
confidence: 99%